Analysis of customer selection and decision model in wildlife conservation projects - Song, Qiurui; Cheng, Wenhao; Liu, Dewang (Transactions on Environment, Energy and Earth Sciences, 2024)
Today, the global illicit hunting of wildlife and illegal trade in wildlife have a detrimental impact on ecosystems, posing a threat to global biodiversity and progressively emerging as the fourth largest illicit trade worldwide. In order to mitigate wildlife trade and safeguard fauna, it is imperative to carefully select appropriate enforcement stakeholders. Based on factors such as visibility, impact, and global reach, this study has identified 20 institutions and organizations out of 50 candidates that align with the client’s criteria. Subsequently, employing a comprehensive evaluation model known as CRITIC-TOPSIS along with 12 indicators, an assessment was conducted to score these 20 organizations. Furthermore, an analysis of their coupling degree was performed which revealed positive coupling effects.